Hurricanes and their implications for unemployment: Evidence from the Caribbean - Preeya Mohan; Eric Strobl (International Labour Organization (ILO), 2021)
Although extreme climate events pose significant challenges to labour markets, there is a paucity of empirical literature studying their impacts. The aim of the study is to investigate the impact of hurricane strikes on unemployment across a sample of Caribbean countries. In breaking down the unemployment data, our findings demonstrate that there is very little difference in the impact for adult males and females as well as male youth, however female youth may be slightly more disadvantaged. Finally, labour legislation appears to provide some mitigating impact from hurricane strikes @Although extreme climate events pose significant challenges to labour markets, there is a paucity of empirical literature studying their impacts. The aim of the study is to investigate the impact of hurricane strikes on unemployment across a sample of Caribbean countries. To do so we constructed a country- and time-varying database of unemployment, hurricane damages, and labour legislation. We then applied a time series cross section model to estimate the contemporaneous and lagged impacts of hurricane destruction. The role of country differences in labour legislation in dampening or exacerbating these effects, was also investigated. Our results suggest that hurricanes in the Caribbean have a downward impact on unemployment, with lagged impacts of up to four years after a disaster strikes. Part of the reason for this fall was a decline in labour force participation rate, however, there was no evidence that greater employment or migration played a role. In breaking down the unemployment data, our findings demonstrate that there is very little difference in the impact for adult males and females as well as male youth, however female youth may be slightly more disadvantaged. Finally, labour legislation appears to provide some mitigating impact from hurricane strikes.
Keywords: 330; labour force participation; unemployment; labour legislation; natural disasters; statistics